NETWORK RESOURCES PLANNING UNTUK IMPLEMENTASI ENTERPRISE SYSTEM DI PERTAMINA - Heral, Hendri
Abstract : Implementation of Enterprise System, such as SAP in Pertamina which has a very wide operation area, must be supported by a large scale network infrastructure with good network performance, so the ES implementation will not produce difficulties to Pertamina operations. The objective of this research is to evaluate re-engineering method for information system network concern with Enterprise System implementation in Pertamina. Main Problem of this re-engineering is a need for increasing bandwidth of least channel (satellite, fiber optic, etc), due to the growth of traffic of SAP implementation that influence network performance. So, traffic demand analysis needed to get accurate bandwidth calculation. The method is Network Resource Planning (NRP). NRP method have 3 cyclic phases, they are baselining phase to collect topology data and to measure existing network utilization, aplication planning phase to estimate aplication traffic demand, and capacity planning phase to calculate bandwidth and to redesign network if it\'s necessary. Two types of tools are used to measure traffic and for capacity planning. In this research network simulation software Opnet is used to validate the calculation results. Implement NRP give optimal network redesign. The design are subnetting in Pertamina Head Quarter and SAP multi instance network configuration that in networking view have the best performance and the lowest channel cost. If it\'s compared with the planning method using SAP formula, this method is more accurate. So this method can be proposed to reengineer the all Pertamina network concern with SAP implementation.